Factors influencing first-time house buyers in Tuaran - George, Enelda Christy (2017)
As the development of towns and cities in Malaysia are persistent, the demand for housing has been increasing every year. This includes Tuaran district, as the town begins to turn into one of the major towns in Sabah. In a housing market, first-time house buyers are important as they indirectly act as an indicator to promoting home ownership. Their preferences are taken into consideration as the basis for estimating the housing demand. Based on literature reviews, there are several factors that have been recognized which could influence the decision-making. The factors include location, environmental, house design, financial and others. In this research, the prominence is to identify the most influential factor on first-time house buyers in Tuaran. In this research, several factors have been identified as they are influential to first-time house buyers. Factors such as environmental, location, house design and financial were identified by analysing responses taken from the target respondent via questionnaires. As for the results, it is known that the environmental factor and financial factor are the main factors that influence the first-time house buyers in Tuaran.